Pelatihan Makanan Tradisional “Kokek” Khas Pasir Pengaraian Guna Melestarikan Kuliner Asli Daerah Kabupaten Rokan Hulu - Aziza Zahira; Melzi Despielni; Aldi Saputra; Musa Thahir; M. Khalilullah (Tasnim Journal for Community Service, 2022)
Riau is one of the provinces in Indonesia with a distinctive culture including the diversity of cuisines and culinary specialties that characterize the culture of the Malay tribe. Rokan Hulu is one of the regencies in Riau which has a special culinary made from durian which is commonly called kokek sour durian. The introduction of the durian sour cocktail was carried out to students at the Vocational High School level, this was done to reintroduce the traditional Rokan Hulu cuisine to young people so they would not be forgotten. The approach method is descriptive qualitative by means of Participatory Action Research (PAR) which aims to learn in solving problems and meeting the practical needs of the community, as well as the production of knowledge. A total of 25 students took part in the kokek cooking training and 92% agreed that this training was very helpful in introducing the durian sour cocktail to students at SMK Zaidar Yahya